Practice of breast sel-examination (BSE) and its relation to knowledge and attitude among female attendees of Out - patient Department, Hospital Kuala Lumpur , 1996 - Rahmah Mohd Amin,; Khadijah Shamsuddin, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Although the effectiveness of Breast Self Examination (BSE) and its potential use as a screening method for detecting early breast cancer is debatable, its practice is useful in raising women's awareness of changes in their breast and body. The Malaysian Ministry of Health has included BSE as one activity of their Healthy Lifestyle Campaign. Public education efforts on BSE are intensified in the printed and electronic media since early 1994. A cross-sectional survey of randomly sampled female attendees of the outpatient clinic, Hospital Kuala Lumpur, aged 20 to 70, was conducted in March 1996. The main purpose was to assess their knowledge, attitude and practice of BSE. Results showed 60.7 % of selected respondents ever practice BSE but only 22.8 % practised it on a monthly basis as recommended. Compared to women who do not practise BSE, women who practised BSE were working, educated to at least secondary education and had family income of more than RM 1001. Total mean score for knowledge was 7.6 ± 2.3 and those with low knowledge consisted only 29.6 % of all respondents. The major sources of knowledge on BSE and breast cancer among these women were television and magazines. Total mean score for attitude among these women was 30 ± 3.1 and 79.4 % of them showed positive attitude towards BSE. The reasons given for not conducting BSE were absence of symptoms and knowledge on how to conduct BSE. This study also showed that BSE practice has a significant relationship with knowledge and attitude of respondents Knowledge was also significantly related with attitude (p values < 0.05 ). Knowledge play an important role in determining the practice of BSE among women. This is evident from logistic regression analysis which showed that knowledge remain significant after controlling selected confounders. In conclusion, despite the high percentage of women exposed to information about BSE and breast cancer, their knowledge and Gonfidence level are still low and only 22.8% respondents practiced BSE monthly as recommended.